Recevez ce mien petit labeur : Studies in Renaissance Music in Honour of Ignace Bossuyt - Berge, Pieter; Delaere, Mark; Bossuyt, Ignace (Book collections on Project MUSE., 2008)
After a distinguished career of more than 35 years, Ignace Bossuyt retired as professor at the Musicology Department of the University of Leuven on October 1st 2007. As an internationally recognised leader in the field of later-16th-century music, Bossuyt consolidated the department's reputation as a centre of excellence in renaissance music studies. Articles in this volume deal with music from the period on which the dedicatee focussed his own research. Subjects discussed include newly discovered music by Philippe de Monte and Heinrich Isaac, humour in the motets of Orlando di Lasso, the begi.